Distinguishing suicide ideation from suicide attempts: Further test of the Integrated Motivational-Volitional Model of Suicidal Behaviour. (October 2019) - Branley-Bell, Dawn; O'Connor, Daryl B.; Green, Jessica A.; Ferguson, Eamonn; O'Carroll, Ronan E.; O'Connor, Rory C.
Abstract: Suicidal behaviour poses a significant public health concern. Research into the factors that distinguish between the emergence of suicide ideation and the enactment of a suicide attempt is crucial. This study tests central tenets of the Integrated Motivational-Volitional Model of suicidal behaviour (IMV, O'Connor and Kirtley, 2018) which posits that volitional phase factors govern the transition from thinking to attempting suicide. 299 adults completed a face-to-face interview and were allocated to groups based on their suicidal history: Suicide attempt group ( N  = 100), suicide ideation group ( N  = 105), and a control group ( N  = 94). Measures were taken at baseline, at 1-month and 6-months follow-up. As predicted, the attempt group differed from the ideation group on all volitional phase factors. Those who had attempted suicide reported higher capability for suicide, were more likely to have a family member or friend who had self-injured or attempted suicide, and were more impulsive. In keeping with the IMV model, the ideation and attempt groups had similar scores on the motivational factors. Defeat and entrapment were significant predictors of ideation at baseline, and mediation analyses indicated that defeat had an indirect effect on ideation through entrapment at baseline and at 1-month follow-up. The results support the IMV model and suggest that entrapment should be routinely included in suicide risk assessments. Further research to test predictors of the transition from suicide ideation to suicide attempts is crucial to inform future intervention development and health care delivery.